Disgust in anorexia nervosa: Testing a theoretical model connecting negative body image to disgust propensity, disgust sensitivity, and self-disgust - Fleur Boonstra; Peter J. de Jong; Rebecca Schulz; Klaske A. Glashouwer (PLoS ONE, 2026)
Consistent with the view that disgust is involved in the persistence of eating disorder symptomatology, it has been found that disgust propensity is related to a negative body image. Importantly, earlier research in non-clinical samples provided preliminary evidence that this relationship could be statistically accounted for by self-disgust. The current study tested the robustness of this finding and examined if this pattern would also be evident when including individuals with and without clinically diagnosed anorexia nervosa (AN). In addition, we tested whether the relationship between self-disgust and negative body image would be especially pronounced in individuals with high disgust sensitivity. Finally, we explored whether body checking and body avoidance could statistically account for the relationship between self-disgust and negative body image. To test these hypotheses, female adolescents with ( n = 64) and without ( n = 62) AN diagnosis completed questionnaires administered online. Results showed that (1) the relationship between disgust propensity and negative body image could be statistically accounted for by self-disgust; (2) disgust sensitivity did not moderate the relationship between self-disgust and negative body image, and; (3) the relationship between self-disgust and negative body image could be statistically accounted for by body checking, but not by body avoidance. Together, these findings are consistent with the view that self-disgust may be an important factor in the persistence of a negative body image in anorexia nervosa.